The pre-judicial inquiry in accordance with the applicable legal norms - Dappa, Rafał (Prawo Kanoniczne, 2018)
Apostolic Letter Motu Proprio of Pope Francis, Mitis Iudex Dominus Iesus, institutes in art. 2 Ratio procedendi, a new procedure for the pre-judicial also called pastoral inquiry. It should take place “in diocesan and parish structures for separated or divorced faithful who have doubts regarding the validity of their marriage or are convinced of its nullity”. It should also lead to getting know the situation of those persons and gathering all useful for the possible judicial course information. It seems that a legislator completely consciously calls the procedure investigatio praeiudicialis in contrast to investigatio praevia presented in can. 1717 - 1719 CIC and in DC, art. 120, §1. They are different according to both, the nature and proceeding and it is not possible to mix or substitute them. Following submission will constitute a comparative analysis of investigatio praeiudicialis included in art. 2 Ratio procedendi CIC/MIDI; investigatio praevia included in art. 120, §1 DC as well as investigatio praevia included in can. 1717-1719 CIC.